Bioethanol Levels from Corn Cob Waste: Effect of Fermentation Time and Saccharomyces cerevisiae Yeast Amount (Zea mays) - Veronika Meiyuina Simatupang; Ramlan Silaban (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
This study aims to determine the highest levels of bioethanol produced through the fermentation process, by looking at the effect of variations in the amount of Saccharomyces cerevisiae, immobilization, and fermentation time, as well as the effect of the amount of Saccharomyces cerevisiae and fermentation time on the ethanol content produced. The highest ethanol content was 39.5 percent in the bioethanol test, with the amount of Saccharomyces cerevisiae 8 grams and fermentation time of 9 days. The treatment given to the number of immobilized Saccharomyces cerevisiae cells and the length of time of fermentation had a major effect on the ethanol content produced, as shown by Anova.